Identification of multiple cell surface antigens associated with the sex pheromone response of Streptococcus faecalis. - Tortorello, M L (1985)
High-molecular-weight surface antigens, obtained by ammonium sulfate precipitation of culture supernatants and identified in Western blots of sodium dodecyl sulfate-polyacrylamide gels, have been correlated with the sex pheromone response of Streptococcus faecalis donor cells. Pheromone-induced cells carrying the conjugative plasmid pCF10 produced both an antigenic component (C130) composed of at least four bands in the range of 130 kilodaltons and a 73-kilodalton antigen (SA 73). The concentration of the C130 antigen in culture supernatants increased with time after exposure of donor cells to pheromone preparations. Gel filtration studies indicated that this antigen exists in the native state as a very large complex that is more than 180,000 daltons in size. The C130 antigen was susceptible to digestion by proteinase K and was not reactive with either concanavalin A or wheat germ agglutinin. The antigenicity of C130 was not destroyed by treatment of blots with trypsin, chymotrypsin, or papain before development with antibody, whereas the antigenicity of SA73 was susceptible to these treatments.